2012
DOI: 10.1080/02640414.2011.640707
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular, biochemical and perceptual post-match fatigue in professional rugby league forwards and backs

Abstract: In this study, we investigated changes in creatine kinase, perceptual and neuromuscular fatigue of professional rugby league players after match-play. Twenty-three male rugby league players (10 backs, 13 forwards) had their creatine kinase, perceptual ratings of fatigue, attitude to training, muscle soreness, and flight time in a countermovement jump measured before and 1 and 2 days after (day 1 and day 2 respectively) league matches. Total playing time, offensive and defensive contacts were also recorded for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
195
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(225 citation statements)
references
References 37 publications
18
195
0
2
Order By: Relevance
“…Previous studies using such protocols have reported impaired jump performance following competitive match-play in Australian football 3,5 , rugby league 4 and soccer 2,6,7 . Although it is important to quantify jump performance following an acute bout of activity (such as a competitive match), it is also of interest to investigate the response to multiple bouts of exercise (such as training regimens).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using such protocols have reported impaired jump performance following competitive match-play in Australian football 3,5 , rugby league 4 and soccer 2,6,7 . Although it is important to quantify jump performance following an acute bout of activity (such as a competitive match), it is also of interest to investigate the response to multiple bouts of exercise (such as training regimens).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of neuromuscular status in team sports in the applied setting have previously included various vertical jumps such as the countermovement jump (CMJ) and the squat jump (SJ) 2,3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Blood and salivary markers have been used to examine the possible mechanisms associated with neuromuscular and perceptual fatigue following team sport competition [7,14,16]. Although testing samples can be expensive, changes in biochemical, hormonal and immunological measures can be easily assessed around daily training activities with non-invasive blood capillary samples and salivary swabs.…”
mentioning
confidence: 99%
“…There are a number of questionnaires that have been used in the literature such as the POMS, RESTQ-Sport and DALDA questionnaires [8,18]. Studies have shown alterations in perceptual fatigue to be more sensitive to tournament competition than jumpderived measures of neuromuscular fatigue [1] and perceived fatigue and muscle soreness are known to outlast suppressed neuromuscular function and biochemical markers following rugby league matches [14]. Increases in perceptual fatigue are suggested to alter an athlete's sense of effort and force them to down-regulate their exercise capacity [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation